The Influence of Cloudiness and Synoptic Situations on the Solar Radiation Balance in the Area of Kaffiøyra (Nw Spitsbergen) in the Summer Seasons 2010 and 2011 - Kejna, Marek; Przybylak, Rajmund; Araźny, Andrzej (Bulletin of Geography. Physical Geography Series, 2012)
This article describes the influence of cloudiness and synoptic situations on individual components of the radiation balance such as: global solar radiation; surface-reflected radiation; longwave terrestrial and atmospheric radiation, and the long- and shortwave balance of two types of ground cover typical to Spitsbergen (the Kaffiøyra region), i.e. morainal and glacial. The research was carried out in the summer seasons of 2010 and 2011, using a Kipp & Zonen CNR4 net radiometer. A substantial influence of the presence of clouds on the individual components of the radiation balance was observed. The type of air masses related to specific synoptic situations was also found to affect the incoming and outgoing solar radiation, as well as its losses.